How do embodied experiences of asthma influence caregiver conceptual models?. (February 2022) - Spray, Julie; Hunleth, Jean; Ruiz, Sienna; Maki, Julia; Fedele, David A.; Prabhakaran, Sreekala; Fechtel, Hannah; Shepperd, James A.; Bowen, Deborah J.; Waters, Erika A.
Abstract: Rationale: Many studies propose that patients', caregivers', and children's asthma management practices may diverge from biomedical recommendations because their understandings of asthma (i.e., conceptual models ) are different from biomedical perspectives. However, little research in this area has examined conceptual models of asthma using embodiment theory, which suggests that caregivers' and children's experiences of the physical body shape their perspectives and consequent management strategies. Objective: We investigated how two embodied processes of symptom perception—detection and interpretation—may influence caregiver or patient conceptions of asthma. Methods: We interviewed 41 caregivers of children with asthma in Gainesville, Florida, and St. Louis, Missouri, and conducted ethnographic visits or virtual interviews with 19 children with asthma aged 6–16. Results: Four aspects of asthma's embodied experience shaped conceptual models via processes of detection and interpretation: 1) symptoms are experienced in the context of other bodily processes; 2) acute symptoms and exacerbations are more salient than their absence; 3) the embodied experience of asthma is one of integrated physiological and emotional processes; and 4) caregivers and children acquire embodied practices of perceiving symptoms that produce embodied knowledge. Conclusion: Participant narratives suggest that embodied experiences of asthma shape caregivers' and children's understandings of asthma in ways that differ from the biomedical model. We argue that a focus on embodied experiences may provide important ground for mutual understanding and communication between providers and caregivers and/or patients. Highlights: Subjective bodily experiences shape caregiver perceptions of their child's symptoms. These embodied symptom perceptions shape caregivers' conceptual models. Caregivers' conceptual models shape their asthma management practices. An embodied view of asthma experience has implications for asthma-related inequities. Recognizing embodied asthma experiences may help providers improve quality of care.